A COMPARATIVE ANALYSIS OF RACISM IN OTHELLO AND THE BLUEST EYE: A CRITICAL RACE THEORY ANALYSIS - Abdullah Saif; Muhammad Zarar; Dr. Alam Zeb (International Journal of Contemporary Issues in Social Sciences, 2024)
Race is a complex social phenomenon that undermines an individual and community based on their skin colour. The current study attempts to analyse racism in Othello (1965) and The Bluest Eye (2007) critically. The theoretical framework utilized for this study is the Critical Race Theory (CRT), developed in the latter half of the 20th century, which holds that race is not a natural or biological construction, rather race is a social construction. The application of CRT on Shakespeare’s Othello and Morrison's The Bluest Eye reveals the downsides of racism. The nature of this study is qualitative and descriptive. The relevant passages from Othello (1965) and The Bluest Eye (2007) have been highlighted and subsequently analysed from the framework of Critical Race Theory (CRT), offering a nuanced examination of themes related to race and power dynamics. The study finds internalized racism in both works. Additionally, this study also finds the presence of individual, institutional and internalized racism in both works. Similarly, this study highlights that racism can turn a sane person into a monster by examining the behaviours of the protagonist of Othello (1965) and Cholly in The Bluest Eye (2007). In addition, it underscores that individual and institutional racism pave the way for internalised racism, which makes the affected community accept all the negative stereotypes about them.